CCBC Choices 2017 - Townsend, Emily McKnight; Schliesman, Megan; Lindgren, Merri V.; Horning, Kathleen T. (Friends of the CCBC, Inc., 2017)
CCBC CHOICES is an annual list of recommended books for children and young adults selected by the librarians at the Cooperative Children's Book Center, a library of the School of Education at the University of Wisconsin-Madison. CCBC CHOICES 2017 recommends 246 titles for children and young adults published in 2016. It includes a commentary on the 2016 publishing year, including statistics on the number of books by and about people of color and from First/Native Nations published for children and teens.
Keywords: Young Adult Literature; Multicultural Literature; Children's Literature